The Effect of the Use of Audio Visual Media on Student Biology Learning Outcomes in The Covid-19 Pandemic Era - Siboro, Thiur Dianti; Purba, Sumarny Tridelpina (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
This research was conducted with the aim of knowing the effect of using audio-visual media on student biology learning outcomes in the covid-19 pandemic era. The approach used in this research is quantitative with the design of One Group Pretest Posttest. The sample of this study was 64 students who were taken by means of Cluster Random Sampling. The data collection technique used was in the form of a learning outcome test consisting of a pretest-posttest and a questionnaire to determine the use of audio-visual media. Based on the results of the study, the average pre-test score for the experimental class was 45.31 and the average pre-test score for the control class was 47.18. The average number of post-test scores for the experimental class was 88.12. The average number of post test scores for the Control class was 86.09. When compared to the average post-test scores for the experimental class, it was greater than the learning outcomes of the control class students. Based on the results of hypothesis testing using the t test, it was obtained that tcount (2.22) > ttable (2.00) at the significance level Î±=0.05 then Ho was rejected and Ha was accepted, meaning that there was a significant effect on student learning outcomes using audiovisual media in the covid pandemic-19 era.